COURSE CONTENT DEVELOPMENT FOR BLENDED LEARNING OF FOREIGN LANGUAGE FOR SPECIFIC PURPOSES - Оксана Мусійовська (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
Nowadays there are many multimedia courses designed to study foreign languages, but their quality is not always relevant to the needs of university education. In terms of blended learning the content of a foreign language course has to meet certain requirements: the educational material must be clearly structured, relevant, illustrative, interesting and accessible, while the interactive nature of educational tasks should stimulate student's creativity and searching activity throughout the training process. This article has defined basic criteria used to select teaching material for the course of "Foreign Language for Specific Purposes" learned by the students of technical universities and grounded the advantages of blended learning technology application in this course.